Strategi Pengelolaan Kurikulum MI Negeri 1 Bandung Barat dalam Peningkatan Kualitas Pendidikan - Ikbal Ropik; Mulyawan Safwandy Nugraha (Journal on Education, 2024)
This study aims to examine the curriculum management strategies of MI Negri 1 West Bandung in an effort to improve the quality of education. Using a qualitative approach with a case study design, this research involved in-depth interviews, participant observation and document analysis. The results showed that MI Negri 1 West Bandung implemented a comprehensive and integrative curriculum management strategy, including: (1) participatory curriculum planning, (2) integration of the national curriculum with local content and Islamic values, (3) technology-based implementation, (4) continuous teacher professional development, and (5) comprehensive curriculum evaluation. This strategy reflects an approach that is adaptive to the demands of modern education, while still maintaining its identity as an Islamic educational institution. The findings make an important contribution to the development of curriculum management models in madrasah ibtidaiyah and can serve as a reference for efforts to improve the quality of basic education in Indonesia. However, further research is needed to measure the long-term impact of this strategy and explore its adaptation in different contexts.